Efektivitas Sosialisasi Narkotika, Psikotropika, dan Zat Adiktif (NAPZA) dalam Meningkatkan Pengetahuan dan Kesadaran Siswa SMP Negeri 05 Sungai Apit - Anugerah Putra, Bayu; Soni, Soni; Gunawan, Rahmad; Fatma, Yulia; Firdaus, Rahmad; Taufiq, Reny Medikawati; Handayani, Fitri; Mukhtar, Harun; Mualfah, Desti; Azim, Fauzan; Aprilya, Regiesta Lintang; Ramadhan, Rafi Fakhri; Abadi, Abdi Nauli (LPPM UMRI, 2026)
The abuse of narcotics, psychotropic drugs, and addictive substances (NAPZA) is a major problem that threatens the future of adolescents, especially junior high school students. Many students do not fully understand the dangers of NAPZA, making them vulnerable to the influence of their surroundings. Therefore, this study was conducted to determine the extent to which NAPZA awareness activities have succeeded in increasing the knowledge and awareness of students at SMP Negeri 05 Sungai Apit regarding the dangers of drug abuse. This study used a qualitative descriptive method with a field study approach. Data were obtained through material presentations and questions given to students after the socialization was conducted. The results showed an increase in students' knowledge about the types of NAPZA, their negative effects, and ways to prevent their abuse. Students were also better able to recognize the factors that could trigger abuse and showed a refusal to try NAPZA. The conclusion of this study states that NAPZA socialization is effective in increasing knowledge and forming a preventive attitude among students at SMP Negeri 05 Sungai Apit. Therefore, activities such as this need to be carried out regularly and continuously to create a healthy, safe, and NAPZA-free school environment.